Influência das espécies não nativas sobre a estrutura funcional das assembleias de peixes de riachos neotropicais com interferências antrópicas - Zavaski, Arielli Giachini (2024)
Functional diversity is represented by biological characteristics of species associated with functionality in the ecosystem, and can be used to detect environmental changes due to human actions, such as the introduction of non-native species. Thus, our objective was to test the effect of land use and occupation and the presence of non-native fish species on the functional structure of fish assemblages in Neotropical streams. Sampling was carried out in 22 streams belonging to the Paraná and Iguaçu river basins, Brazil, using electrofishing. Significant relationships between functional traits and non-native species and urbanization were detected by redundancy analysis. Significant correlation was recorded between functional dispersal (FDis) and the proportion of non-native species. Therefore, we conclude that non-native species introduced new traits, increasing FDis and altering the composition of the functional structure of the urbanized stream community.